The Moderating Role of Government Support on Food Processing SME’s Internal Factors and the Impact to Export Performance - Chelliah, Shankar; Lee, Ming Huoy (International Journal of Asian Social Science, 2020)
This research addresses a theoretical framework to describe the relationship between firm characteristics, management characteristics, labour productivity, innovation and moderating effect of government support on food processing SMEs’ export performance. The new conceptual framework helps firms to determine the factors that contribute to the success in export performance and the effectiveness of government support. The research is focusing on food processing firms because the food processing industry is considered one of the most value-added businesses in the Malaysian economy. The results indicated that food processing firms’ export performance is positively related to firm characteristics, management characteristics, labour productivity, and innovation. Government support is an important element to strengthen food processing SMEs’ export performance, the moderating effect from government support, shown a significant positive relationship between management characteristics and labour productivity towards export performance, but the lesser moderating effect is shown towards firm characteristics and innovation. The government support has created a platform and rich resources to expand firm networking, management skills, and labour skills. Continue effort required for improving firms’ firm characteristics and innovation.